Security Issues and Research Challenges in Cloud Computing (International Journal of Engineering and Computer Science, 2024)
Cloud Computing is a type of internet based computing which provides services via the internet and accesses the resources within the user enterprise either in a private-own-cloud or on a third-party server On Demand. The model is characterized by three attributes: scalability, pay-per-use, self-services. Many industries such as banking, healthcare, Retail, Education, Manufacturing and business are adopting this cloud technique due to efficiency of services provided by pay-per-use pattern which helps in accessing the networks, storage, servers, services and applications, without physically acquiring them [3]. The circumscribed control over the data may cause various security issues in cloud computing like Data crash, Misuse and reprehensible use of cloud computing, Insecure API, Wicked Insiders, Shared technology issues/multi-tendency nature, Account services and Traffic Hijacking. There are many new technologies, improvements and research proceedings happening every day in order to develop the security and to provide assurance for users [2]. This research paper brings a framework on what cloud computing is, main security risks and issues that are currently present in the field of cloud computing, research challenges, importance in key industries and also the personal hypothesis on future advances in the field of cloud security.